A comparative simulation study of different decoding schemes in LDPC coded OFDM systems for NB-PLC channel - Nejwa El maammar; Seddik Bri; Jaouad Foshi (Institute of Advanced Engineering and Science, 2019)
In this paper, we study the performance of Low density Parity Check (LDPC) coded orthogonal frequency-division multiplexing (COFDM) systems when they are applied on the short data block of a narrowband (NB) power line communications (PLC) channel. In the modelled system simulations have been performed using different code lengths. It is assumed that the channel has a multipath propagation with two different noise scenarios: AWGN background noise with and without the presence of impulsive noise. Performances of Various soft and hard decision LDPC decoder schemes such as belief propagation (BP), weighted bit flipping (WBF), improved weighted bit flipping (IWBF) and implementation-efficient reliability ratio based weighted bit flipping (IRRWBF) decoders were investigated. It has been shown for all simulations performed in PLC channel model showed that remarkable performance improvement can be achieved by using short-length LDPC codes. Especially, the improvements are striking when the BP decoding algorithms are employed on the receiver side.